The structure of aspartyl dipeptidase reveals a unique fold with a Ser-His-Glu catalytic triad - Håkansson, Kjell (The National Academy of Sciences, 2000)
The three-dimensional structure of Salmonella typhimurium aspartyl dipeptidase, peptidase E, was solved crystallographically and refined to 1.2-Å resolution. The structure of this 25-kDa enzyme consists of two mixed β-sheets forming a V, flanked by six α-helices. The active site contains a Ser-His-Glu catalytic triad and is the first example of a serine peptidase/protease with a glutamate in the catalytic triad. The active site Ser is located on a strand–helix motif reminiscent of that found in α/β-hydrolases, but the polypeptide fold and the organization of the catalytic triad differ from those of the known serine proteases. This enzyme is a member of a family of serine hydrolases and appears to represent a new example of convergent evolution of peptidase activity.